Farmland use transition and its spatial spillover effect in the Dongting Lake region - Tang, Yifeng; Tan, Zhongyi; Jiang, Youlei; Ouyang, Sili; Sun, Wenbo; Lu, Xinhai; Wang, Hongzheng (Frontiers in Sustainable Food Systems, 2025)
The policy of returning farmland to wetland in the Dongting Lake Region (DLR) is devised to foster synergy between grain production and ecological protection, while also effectively mitigating land degradation. However, the connotations and the spatial spillover effect of farmland use transition (FUT) in this region remain insufficiently understood. To address these gaps, this study deconstructs the FUT through farmland spatial transition, functional transition and model transition. By using the Sparrow Search Algorithm-Projection Pursuit Model for evaluation, this study analyzes the spatiotemporal pattern evolution characteristics of FUT. Additionally, spatial econometric model is employed to examine the spatial spillover effect of FUT. The results demonstrate that FUT in the DLR showed a fluctuating but overall upward trend. Spatial transition represents an ordinal covariate of model transition, and the two entities together form a mechanism for synergistic evolution that exhibits a biased symbiotic relationship. Strengthening the positive spillover effects of political and socio-economic drivers could promote more balanced FUT. These findings provide a theoretical basis for integrating ecological restoration with sustainable agricultural development in the DLR.